Dioxins and dioxin-like PCBs in the ambient air of the Valencian Region (Spain): Levels, human exposure, and risk assessment. (March 2021) - López, Antonio; Coscollà, Clara; Hernández, Cristina S.; Pardo, Olga; Yusà, Vicent
Abstract: Dioxins (polychlorinated dibenzo-p-dioxins (PCDD) and polychlorinated dibenzofurans (PCDF), as well as dioxin-like PCBs (dl-PCBs), are listed as persistent organic pollutants in the Stockholm Convention. In this study, we measured their concentrations in the particulate phase (PM10) of the ambient air in seven monitoring stations of the Valencian Community (Spain). A total of 82 samples were collected from different sampling sites: four industrial, two urban, and one remote, from February to December 2019. The total concentrations of the sum of PCDD, PCDF, and dl-PCBs ranged from 2.90 fg TEQ/m 3 to 317.98 fg TEQ/m 3 . Risk assessment for adults and children was performed using both daily and chronic exposure. Each station showed its specific dioxin profile, related to the main productive activities in each area. The daily inhalation dose (DID) in adults and children was lower than the tolerable daily intake (TDI) of 1–4 pg WHO TEQ kg −1 b.w. d −1 for dioxins. In the case of chronic exposure, the cancer risk for dioxins and dl-PCBs was estimated at values ranging from 5.27 E−07 to 5.52 E−05. The cancer risk for dioxins and PCBs estimated at the 95th percentile was higher than 1.0 E−06 in all of the industrial and urban areas. Graphical abstract: Image 1 Highlights: Total concentrations of PCDD/Fs and dl-PCBs ranged from 2.9 to 318 fg TEQ/m 3 . Risk assessment was carried out using daily exposure and chronic exposure. Inhalation exposure for adults and children was below the TDI. Cancer risk (p95) was higher than 1.0 E−06 in six evaluated areas.